Efektivitas Acceptance Commitment Therapy dalam Meningkatkan Subjective Well-Being pada Dewasa Muda Pasca Putusnya Hubungan Pacaran - Sri Juwita Kusumawardhani; E. Kristi Poerwandari (Fakultas Psikologi Universitas Pancasila, 2018)
Romantic relationship is one of the most important assets for individual’s self esteem, health and happiness or their subjective well-being (Reis, Collins, & Berscheid, 2000). By that fact, the broke-up of the romantic relationship can decrease the level of happiness and subjective well-being of individuals whether the subjective well-being itself is relatively stable for the entire life (Park & Sanchez, 2007). Sometimes an individual responded their broke-up by doing some maladaptive acts such as an endless emotional distress and obsessive act just to get back their ex-partner. The purpose of this research is to give Acceptance Commitment Therapy (ACT) in order to enhance people’s happiness. The research design is using one group pretest-postest design. As a partisipant, young adult should be in 20 until 40 years of age. This intervention contains 5 (five) session which held once in a week and the duration is ± 90 minutes per session. Based on the quantitative evaluation with Oxford Happiness Questionnaire and Core Bereavement Item, and also the qualitative evaluation from observation and interview, the main result pointed that Acceptance Commitment Therapy is effectively proven to increase subjective well-being in Young Adults’ post relationship dissolution.